LANDSLIDE SUSCEPTIBILITY MAPPING USING GIS-BASED MULTI-CRITERIA DECISION ANALYSIS METHOD - Saragih, Darman Ferianto; Ginting, Bertha Br (JURNAL TEKNIK SIPIL, 2023)
Changes in land use (triggered by population growth), economic, social, cultural development, climatic conditions, geology, and topography of an area cause more landslides to occur. Depending on the location, it often causes a much of loss, both in the form of property and human lives. The GIS (Geographical Information Systems) is beneficial for managing the geographic data, and MCDA (Multi-Criteria Decision Analysis) is applied to evaluate various criteria for making decisions that often conflict, such as the criteria for triggering the landslide. The research aims to enrich the application of the GIS-based MCDA method in determining the landslide hazard mapping model and its application to create a landslide susceptibility map of the area under study. The sequence of the landslide susceptibility mapping model steps applied in this study is as follows: 1) Determination of evaluation criteria, 2) data/maps collection, 3) Criteria standardization, 4) Creating the standardized criteria maps, 5) Criteria weighting, and 6) Criteria maps combinations. The model result is a map showing the distribution of areas that have different levels of landslide susceptibility. Most of the study areas (67.24 %) have moderate levels, 17.84 % high, and only 1.70 % very high levels of susceptibility.